When the Going Gets Rough: The Significance of Brucella Lipopolysaccharide Phenotype in Host–Pathogen Interactions - Stranahan, Lauren W.; Arenas-Gamboa, Angela M. (Frontiers in Microbiology, 2021)
Brucella is a facultatively intracellular bacterial pathogen and the cause of worldwide zoonotic infections, infamous for its ability to evade the immune system and persist chronically within host cells. Despite the frequent association with attenuation in other Gram-negative bacteria, a rough lipopolysaccharide phenotype is retained by Brucella canis and Brucella ovis, which remain fully virulent in their natural canine and ovine hosts, respectively. While these natural rough strains lack the O-polysaccharide they, like their smooth counterparts, are able to evade and manipulate the host immune system by exhibiting low endotoxic activity, resisting destruction by complement and antimicrobial peptides, entering and trafficking within host cells along a similar pathway, and interfering with MHC-II antigen presentation. B. canis and B. ovis appear to have compensated for their roughness by alterations to their outer membrane, especially in regards to outer membrane proteins. B. canis, in particular, also shows evidence of being less proinflammatory in vivo, suggesting that the rough phenotype may be associated with an enhanced level of stealth that could allow these pathogens to persist for longer periods of time undetected. Nevertheless, much additional work is required to understand the correlates of immune protection against the natural rough Brucella spp., a critical step toward development of much-needed vaccines. This review will highlight the significance of rough lipopolysaccharide in the context of both natural disease and host–pathogen interactions with an emphasis on natural rough Brucella spp. and the implications for vaccine development.